1980
DOI: 10.1302/0301-620x.62b1.7351432
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy and arthrography of the knee: a critical review

Abstract: A series of 135 knee arthroscopies has been reviewed to determine the accuracy of detection of meniscal lesions. Arthroscopy and double-contrast arthography achieved similar accuracy (84 per cent and 86 per cent) in the diagnostically more difficult knees of the series. The combined accuracy of both examinations was 98 per cent. Arthroscopic difficulty in seeing the posterior third ofthe medial meniscus, and consequently tears in this region, is emphasised and discussed. Arthroscopy and arthrography are comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 0 publications
1
25
1
Order By: Relevance
“…Furthermore, the diagnosis at follow-up examination was in good agreement with the diagnosis at the initial arthroscopy, when correlated for the 1 1 diagnostic failures. Our results tend to support most of the previously reported results (Jackson & Abe 1972, DeHaven & Collins 1975, McGinty & Freedman 1976, Gillquist et al 1977, Ireland et al 1980) that arthroscopy offers a substantial increase in the diagnostic accuracy of meniscal lesions and tears of the anterior cruciate ligament. In contrast, Gillies & Seligson (1977) found the arthroscopic accuracy in meniscal lesions as low as 68 per cent, whereas their clinical accuracy was 85 per cent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the diagnosis at follow-up examination was in good agreement with the diagnosis at the initial arthroscopy, when correlated for the 1 1 diagnostic failures. Our results tend to support most of the previously reported results (Jackson & Abe 1972, DeHaven & Collins 1975, McGinty & Freedman 1976, Gillquist et al 1977, Ireland et al 1980) that arthroscopy offers a substantial increase in the diagnostic accuracy of meniscal lesions and tears of the anterior cruciate ligament. In contrast, Gillies & Seligson (1977) found the arthroscopic accuracy in meniscal lesions as low as 68 per cent, whereas their clinical accuracy was 85 per cent.…”
Section: Discussionsupporting
confidence: 91%
“…plement to arthroscopy, undoubtedly would have increased our arthroscopic accuracy, especially in tears of the anterior cruciate ligament and in lesions of the posterior horn of the menisci as these lesions can be difficult to expose arthroscopically (Gillies & Seligson 1979, Ireland et al 1980.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the false negative results seem to occur exclusively from misinterpretation of MRI. 14,15 As far as the cruciate ligaments are concerned, our study showed that from the 28 ACL ruptures diagnosed during arthroscopy 04 of them were negative; leading to NPV of MRI for ACL ruptures of 66.6%. The accuracy, sensitivity and specificity values for knee lesions vary widely in literature.…”
Section: Discussionmentioning
confidence: 80%
“…Although arthrography and arthroscopy have made it possible to initiate prompt treatment, there are still difficulties in detecting tears of the lateral meniscus [1,4,5] and the posterior horn of the medial meniscus [9,15].…”
Section: Introductionmentioning
confidence: 99%